A NOVEL GENETIC MARKER FOR INHERITED DISORDER OF THE HEART CONDUCTION SYSTEM - S. Yu. Nikulina; A. A. Chernova; S. S. Tretyakova (Российский кардиологический журнал)
Aim. To study relation of mononucleotide polymorphism G>A of the gene SCN10A and development of inherited pathology of the heart conduction system.Material and methods. Totally, 260 persons investigated with primary disorders of cardiac conduction (71 patient with atrioventricular conduction disorder, 84 patients with the Right His bundle branch conduction disorder and 105 — the Left) and 263 persons without any found cardiovascular diseases (controls). All patients underwent standard cardiological investigation, retrospective analysis of previous investigation data (if available), molecular genetic test of DNA.Results. The obtained results showed statistically significant predominance of the widespread genotype GG gene SCN10A in the control group comparing to atrioventricular disorder patients and Right His bundle branch patients.Conclusion. Homozygous genotype GG of the gene SCN10A plays protective role against development of idiopathic atrioventricular blocks and Right His bundle branch block.